Cultivo de yacon em duas condições edafoclimáticas e épocas de plantio no sul do Espírito Santo - Silva, Diego Mathias Natal da (2015)
Consumption of yacon has presented numerous health benefits, which opens the expectations of its cultivation as a new product to be explored and applied to social, agricultural, technological and scientific levels. Nevertheless, in Brazil the area under c